2011
DOI: 10.1159/000327501
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin in Allergic Inflammation

Abstract: Thioredoxin (TRX) is a redox-active protein that regulates reactive oxidative metabolism and plays a crucial role in the antioxidant system in regulating the reduction/oxidation balance by scavenging reactive oxygen species, which is implicated in the mechanism of asthma. As for the mechanisms by which TRX exerts its beneficial effects, some studies have shown that TRX suppresses allergic inflammation in animal models of asthma. Recently, we reported that TRX directly modulated the chemotaxis of eosinophils, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…These experimental observations suggest that cellular activation is well regulated in eosinophils transiting the blood stream and EETosis is mainly occurring within inflamed tissue or after luminal entry [53]. Simultaneously, the oxidant-antioxidant imbalance in allergic diseases [54, 55] might favor the development of EETosis. Tight regulation of ETosis appears to be critical for minimizing unnecessary autoimmunity and sterile inflammation [56].…”
Section: Eosinophil Etosismentioning
confidence: 99%
“…These experimental observations suggest that cellular activation is well regulated in eosinophils transiting the blood stream and EETosis is mainly occurring within inflamed tissue or after luminal entry [53]. Simultaneously, the oxidant-antioxidant imbalance in allergic diseases [54, 55] might favor the development of EETosis. Tight regulation of ETosis appears to be critical for minimizing unnecessary autoimmunity and sterile inflammation [56].…”
Section: Eosinophil Etosismentioning
confidence: 99%
“…In low/moderate concentration of ROS are essential for maintaining normal physiological functions, but excess productions and/or decreased levels in antioxidant(s) lead to oxidative stresses [7,18,19]. TRX is well known to be one of the most important regulators of reduction/oxidation (redox) balance and to inhibit intracellular ROS generation [11][12][13]20], which causes tissue injury at the inflamed site during AR [21,22]. It is reported that TRX suppressed the CC chemokine-induced chemotaxis of eosinophils through inhibition of both activation of extracellular signal-regulated kinase 1/2 and p38 mitogen-activated protein kinase pathways [22], which play an important role in eosinophil chemotaxis [23].…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 and IL-5) production induced by inhalation of specific allergen [11,12]. Furthermore, TRX is reported to inhibit the production of regulated on activation, normal T cell expressed, and secreted (RANTES)-and eotaxin-induced migration of eosinophils, leading to attenuation of eosinophilic inflammatory responses in airways [13]. Although these reports strongly suggest that TRX plays a crucial role in the development of allergic diseases and will be a good target in the treatment of airway eosinophilic inflammatory disease, the influence of histamine H1 receptor antagonists, which are frequently used for the treatment of airway allergic diseases with remarkable success, is not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…BAP is measured as the reductive ability of antioxidants such as vitamin C, vitamin E, uric acid, and reduced glutathione in the serum (40). In addition, TRX plays an essential role in cellular function and protection by limiting oxidative stress directly via its antioxidant effects; TRX expression is enhanced by acute exercise (41). A previous study reported that exercise training increased TRX levels in the rat brain (42).…”
Section: Discussionmentioning
confidence: 99%